2018
DOI: 10.1111/ijcs.12438
|View full text |Cite
|
Sign up to set email alerts
|

A Spanish perspective on the impact on religiosity and spirituality on consumer ethics

Abstract: Studies of consumer ethics have generally used the Muncy–Vitell consumer ethics scale, but much of the published research has encountered problems with this scale. The present study proposes a new perspective for assessing consumer ethics, which constructs a model to analyze the impact of religiosity and spirituality on consumer attitudes and whether it leads to either ethical or unethical behaviour. Our model indicates that consumers’ behaviour in situations that involve ethical issues partly depends on both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 92 publications
1
33
0
5
Order By: Relevance
“…Religiosity is one of the key components of social behavior and directly and indirectly influences consumers and society [16]. For instance, Vitell et al [38] claimed that religiosity affects consumers' behaviors in situations that involve ethical issues. Likewise, Forghani et al [39] reported that religiosity is documented as an important aspect that deeply impacts consumer buying decisions.…”
Section: Religiosity and Food Waste Intentionmentioning
confidence: 99%
See 1 more Smart Citation
“…Religiosity is one of the key components of social behavior and directly and indirectly influences consumers and society [16]. For instance, Vitell et al [38] claimed that religiosity affects consumers' behaviors in situations that involve ethical issues. Likewise, Forghani et al [39] reported that religiosity is documented as an important aspect that deeply impacts consumer buying decisions.…”
Section: Religiosity and Food Waste Intentionmentioning
confidence: 99%
“…Saudis place a high value on generous hospitality and a gesture of welcome by providing plentiful food to their guests to exceed their expectations. This kind of culture and practices simply lead to food waste, particularly during the festivals of Eid, weddings, and parties wherever take place at home or in restaurants, where it is common for lavish banquets to be presented with lots of fresh and abundant food [35][36][37][38]. The KSA food consumption culture is clearly presented during the Ramadan month as well as Hajj seasons.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Vitell et al. (2018) argued that religiosity affects consumers’ behaviours in situations that involve ethical issues. Similarly, Siyavooshi et al.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Minton, Kahle, Jiuan, and Tambyah, (2016), based on the model of Allport and Ross (1967), conceptualized the construct of religiosity as intrinsic religiosity and extrinsic religiosity. Intrinsic religiosity is related to personal objectives and describes inner spirituality objectives, while extrinsic religiosity describes social descriptions of individuals' religiousness (Arli & Tjiptono, 2018;Vitell, Ramos-Hidalgo, & RodrÃŋguez-Rad, 2018). Further, religiosity is acknowledged as the predictor of behaviors and value systems (Hwang, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%